ESTUDO DA INFECÇÃO E DOENÇA NO CÃO (Canis familiares) POR Leishmania (Leishmania) chagasi EM UMA ÁREA ENDÊMICA NA ILHA DE SÃO LUÍS-MARANHÃO, BRASIL - Garcia, Arnaldo Muniz (2004)
A cohort prospective study was carried with 350 dogs of various ages at localities Vila Nova and Bom Viver in the municipality of Raposa-MA, from March of 2002 to December of 2003. The objective is to avaluate the behavior of L. (L.) chagasi infection. The chosen areas are a result of the disordered occupation process, contributing with 60% of LVH and LVC cases that were notified by the municipal district. At first, the procedure was made by doing the populational inquiry the two places by means of canine census. The study was processed in two phases, with interval of 7 months among the same ones. In the first phase, 350 dogs participated of the study and by a visiting process a questionnaire with epidemiological, demographical, clinical and behavioral data about the dogs was applied. The testing of Montenegro intradermoreaction (IDRM) was made with the antigen of L. (L.) amazonensis and adapted for dogs, serological examination testing Enzyme Linked Immunsorbent Assay (ELISA), clinical e parasitical were also made in positive animals to IDRM and/or ELISA tests. Starting from clinical and immunological parameters already referred in literature, were defined four diagnoses categories, classifying the dogs according to its evolutionary course in not infected dogs (195), infected (100), Oligosymptomatic sick (41) and polysymptomatic sick (14). The second phase was accomplished with application of the same tests of the first phase with 230 dogs, that reduction was due in function of the losses (36,28%) caused by death, address change and missing. The positive dogs for an or both tests were accompanied bimonthly with reevaluation of the clinical exams. The initial and final prevalence and incidence of the infection were 8,57%, 6,52% and 8% for IDRM; by ELISA 39,71%, 32,6% and 16%; for ELISA and IDRM 44,29%, 37,39% and 21,6% respectively. In what the clinical form refers, the dogs were classified in the following way: infected (28,57%), oligosymptomatic sick (11,71%) and polysymptomatic sick (4%). in agreement with the statistical analyses not adjusted and adjusted, the variable age, race, secondary lesion, physical condition and place were associated the infection for L. (L.) chagasi. The infection for L. (L.) chagasi was present in 52,97% of the canine population of Vila Bom Viver and 34,55% in Vila Nova, demonstrating that in endemic area happens the intense and active circulation of Leishmania.